2012
DOI: 10.1002/uog.10082
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interobserver variability in fetal ultrasound measurements

Abstract: Although intra- and interobserver variability increases with advancing gestation when expressed in millimeters, both are constant as a percentage of the fetal dimensions or when reported as a Z-score. Thus, measurement variability should be considered when interpreting fetal growth rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 28 publications
10
145
3
5
Order By: Relevance
“…Inaccurate measurements can lead to erroneous detection of fetal growth restriction or macrosomia leading to unnecessary intervention, maternal anxiety and iatrogenic perinatal morbidity; or may lead to inaccurate identification of growth-restricted fetuses as normal [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inaccurate measurements can lead to erroneous detection of fetal growth restriction or macrosomia leading to unnecessary intervention, maternal anxiety and iatrogenic perinatal morbidity; or may lead to inaccurate identification of growth-restricted fetuses as normal [18].…”
Section: Discussionmentioning
confidence: 99%
“…This trend is known to be more pronounced for HC and AC than for FL [18]. However, studies have also shown good intraand inter observer reproducibility of ultrasound measurements of fetal biometry [25][26][27].…”
Section: Papermentioning
confidence: 94%
“…Reliability was confirmed within 7.5% for the measurements taken by the sonographer compared with ENH. Recent work has compared the inter‐observer reliability when performing fetal biometry with 95% limits of agreement for AC ± 8.8% 28 . Although it was possible that the results would be affected by the relative inexperience of ENH and the fact that that AC measurement is difficult to measure reliably, particularly in the third trimester, 29 , 30 the data showing accuracy for the AC measurement are reassuring.…”
Section: Discussionmentioning
confidence: 99%
“…Prvi razlog je da je većina studija koje su analizirale ponovljivost različitih ultrazvučnih merenja u akušerstvu koristila ovaj metod, što daje mogućnost adekvatnije diskusije postignutih rezultata (Bland et Altman, 1990;Brennan et Silman, 1992;Sarris et al, 2012). Drugi razlog je njegova prednost u objektivnijem tumačenju rezultata ove studije, obavljene kod trudnica u drugom i trećem trimestru trudnoće, jer njegova evaluacija uzima u obzir i različitu gestacionu starost (Sarris et al, 2012). Iako bi različita fetalna prezentacija, intenzivirana fetalna aktivnost i povećani BMI (koji se često viđaju u trudnoćama komplikovanim GDM-om) mogli otežati pregled i povećati varijabilnost merenja, rezultati disertacije nisu ispunili ova očekivanja.…”
Section: Procena Pouzdanosti Ultrazvučnog Skora U Otkrivanju šEćerne unclassified
“…Iako bi različita fetalna prezentacija, intenzivirana fetalna aktivnost i povećani BMI (koji se često viđaju u trudnoćama komplikovanim GDM-om) mogli otežati pregled i povećati varijabilnost merenja, rezultati disertacije nisu ispunili ova očekivanja. Uvidom u literaturne podatke, ustanovljeno je da su i drugi autori došli do zaključka da pomenute varijable i faktori nisu značajno uticali na varijabilitet (Harstad et al, 1994;Sarris et al, 2012). Značaj ove studije ogleda se i u tome što je u nju uključen i veliki broj trudnica sa povišenim vrednostima BMI (maksimalna BMI vrednost u momentu ultrazvučnog pregleda u studijskoj populaciji iznosila je 47.47), a s obzirom da je to i jedan od mogućih inkluzionih kriterijuma, a za razliku od nekih prethodnih studija koje su kao gornji limit BMI imali vrednost od 29.9 (Sarris et al, 2012).…”
Section: Procena Pouzdanosti Ultrazvučnog Skora U Otkrivanju šEćerne unclassified